2010
DOI: 10.1136/bjo.2008.147538
|View full text |Cite
|
Sign up to set email alerts
|

Vision self-management for older adults: a randomised controlled trial

Abstract: Background/aims Ageing of the population will result in unprecedented numbers of older adults living with agerelated vision loss (ARVL). Self-management models improve health outcomes and reduce healthcare costs; however, the principles have rarely been applied in low vision services. Methods A two-armed randomised controlled trial of older adults (n¼77) with ARVL compared 'usual care' provided by a not-for-profit community agency with an extended model of care (usual care+self-management group intervention). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 17 publications
2
113
3
Order By: Relevance
“…143 This RCT included a waiting list control, full details of randomisation and masking (with a specified protocol for avoiding the disclosure by patients of their intervention group), the use of a range of well-validated outcome measures, and full details of results. It may be that the publication of this report, and others with a similarly rigorous protocol development (Girdler et al 60 …”
Section: Figure 1 About Herementioning
confidence: 99%
See 4 more Smart Citations
“…143 This RCT included a waiting list control, full details of randomisation and masking (with a specified protocol for avoiding the disclosure by patients of their intervention group), the use of a range of well-validated outcome measures, and full details of results. It may be that the publication of this report, and others with a similarly rigorous protocol development (Girdler et al 60 …”
Section: Figure 1 About Herementioning
confidence: 99%
“…The intention to treat analysis showed that the extended model produced significantly improved participation levels and the belief in the ability to manage every day tasks. 60 Other studies have evaluated the effects of more specialised services. For example, Engel et al and Kuyk et al demonstrated significant improvements in mobility-related ADLs after specific orientation and mobility training programmes, although it was not possible to calculate effect sizes from the data presented.…”
Section: Effect Of Rehabilitation On Visual Function and Activitiementioning
confidence: 99%
See 3 more Smart Citations